A new species of Pinnixa (Crustacea: Decapoda: Brachyura: Pinnotheridae) associated with a tube worm, Chaetopterus cautus (Annelida: Polychaeta), from Tokyo Bay, Japan - Komai, Tomoyuki; Nishi, Eijiroh; Taru, Masanori (Zootaxa, 2014)
A new species of the pea crab genus Pinnixa White, 1846 (Pinnotheridae), P. banzu n. sp., is described and illustrated on the basis of four specimens from Banzu, an estuary of the Obitsu River, Kisarazu, Chiba Prefecture, Japan. All the specimens examined were associated with the polychaete tube worm Chaetopterus cautus Marenzeller, 1879 (Chaetopteridae). The new species is very similar to P. chaetopterana Stimpson, 1860 from the western Atlantic, P. occidentalis Rathbun, 1894 from northwest North America, and P. rathbuni Sakai, 1934 from East Asia. It is distinguished from the latter three species by characters of the carapace, ambulatory legs, male abdomen, and male first gonopod. It is suggested that previous records reporting on the association of P. rathbuni with Chaetopterus tube worms might be actually referred to the new species.